MULTI-SOURCE SATELLITE OBSERVATIONS REVEAL EVOLUTION PATTERN OF RIFTS IN THE FILCHNER-RONNE ICE SHELF, ANTARCTICA - R. Li; R. Li; D. Lv; D. Lv; H. Xiao; H. Xiao; S. Liu; S. Liu; Y. Cheng; Y. Cheng; G. Hai; G. Hai; et al. (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
This paper presents a systematic fracturing study of the Filchner-Ronne Ice Shelf (FRIS) in Antarctica based on multisource data dating back to 1973. Two fracture maps of FRIS were extracted from Landsat-8 OLI images of 2014–2015 and MODIS mosaic of Antarctica (MOA) 2008–2009. The evolution pattern and temporal change of two crucial rifts, Rifts T1 and T2 are analysed for their similarities with the Grand Chasm, which directly induced the previous major calving event of Filchner Ice Shelf (FIS) in 1986. The depth temporal change of Rift T2 was also analysed based on ICESat altimetry data and DEMs reconstructed from ZY-3 and WV-2 stereo images. 3D parameters were also extracted and analysed from DEMs, including rift depth, walls, mélange surface roughness, and mélange thickness. In total, 582 new fractures were extracted from 2004 to 2009 and another 752 from 2008 to 2015. Rifts T1 and T2 showed high activeness, which experienced a rapid growth of 82% and reached ∼50 km in length. Based on all the observations of fracture and rift activity, some regions of ice shelf front in RIS and FIS show some important characteristics that can be related back to the previous calving events.